NILAI KARAKTER SASTRA ANAK: KORELASI ANTARA NOVEL ANAK DAN PEMBELAJARAN DI SEKOLAH DASAR - Rudi Umar Susanto; Syamsul Ghufron; Novi Rahmania Aquariza (ELEMENTARY: Jurnal Inovasi Pendidikan Dasar, 2026)
This study aims to examine the character values embedded in children’s literature, particularly children’s novels, and to analyze their correlation with learning processes in elementary schools. The focus of the study is directed toward the use of children’s novels as learning media that contribute to the formation and strengthening of students’ character. This research employs a descriptive qualitative approach by analyzing several popular children’s novels that are widely read or relevant to the world of children. The analysis is conducted by identifying character values reflected through characters, plot, conflicts, and moral messages in the novels, and then relating these values to their application in classroom learning contexts. The results indicate that children’s novels contain various positive character values, including honesty, responsibility, cooperation, empathy, discipline, and independence, which are aligned with the objectives of character education in elementary schools. Furthermore, children’s novels are able to present learning experiences that are more contextual, engaging, and meaningful, thereby facilitating students’ understanding and internalization of character values in a natural way. Therefore, children’s literature, particularly children’s novels, has significant potential to be utilized as learning media and resources in supporting the implementation of character education in elementary schools. ABSTRAK Penelitian ini bertujuan untuk mengkaji nilai-nilai karakter yang terkandung dalam sastra anak, khususnya novel anak, serta menganalisis korelasinya dengan pembelajaran di sekolah dasar. Fokus penelitian diarahkan pada pemanfaatan novel anak sebagai media pembelajaran yang berperan dalam pembentukan dan penguatan karakter peserta didik. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan teknik analisis terhadap sejumlah novel anak yang populer dan banyak digunakan atau relevan dengan dunia anak. Analisis dilakukan dengan mengidentifikasi nilai-nilai karakter yang tercermin melalui tokoh, alur, konflik, dan pesan moral dalam novel, kemudian mengaitkannya dengan penerapan nilai tersebut dalam konteks pembelajaran di kelas. Hasil penelitian menunjukkan bahwa novel anak mengandung berbagai nilai karakter positif, antara lain kejujuran, tanggung jawab, kerja sama, empati, disiplin, dan kemandirian, yang sejalan dengan tujuan pendidikan karakter di sekolah dasar. Selain itu, novel anak mampu menghadirkan pembelajaran yang lebih kontekstual, menarik, dan bermakna, sehingga memudahkan peserta didik dalam memahami serta menginternalisasi nilai-nilai karakter secara alami. Dengan demikian, sastra anak, khususnya novel anak, memiliki potensi yang signifikan untuk dijadikan sebagai media dan sumber pembelajaran dalam mendukung pelaksanaan pendidikan karakter di sekolah dasar.